The Role of Short-Term Memory in Understanding Spoken Language: A Study Inspired by Finding Dory - Fauzyah, Martizha; Listiani, Toneng; Wardoyo, Cipto (Program Studi Pendidikan Bahasa Inggris, 2025)
This research investigates the role of short-term memory (STM) in the comprehension of spoken language from a psycholinguistic perspective. Anchored in the theoretical frameworks of Alvarez & Cavanagh (2004), Norris (2017), and Jonides et al. (2008), the study explores how impairments in STM disrupt verbal processing, including the ability to retain, decode, and respond to linguistic input in real time. The analysis centers on Dory, a fictional character in Pixar’s Finding Dory (2016), who is depicted as experiencing persistent short-term memory loss. Employing a qualitative descriptive approach and narrative analysis, twenty scenes were selected to examine manifestations of memory-related language breakdowns in naturalistic conversational contexts. The findings reveal consistent disruptions in Dory’s verbal interactions, particularly in turn-taking, following instructions, and interpreting social cues—phenomena that align with contemporary models of STM as a distinct cognitive system from long-term memory. While emotionally salient information is occasionally retained, the character’s inability to maintain immediate verbal context leads to confusion and emotional distress. These results underscore both the linguistic and psychosocial consequences of STM deficits. By integrating psycholinguistic theory with narrative media, the study provides accessible insight into cognitive-linguistic disorders. Future research should explore real-world populations to substantiate these findings and inform educational or clinical interventions.